The role of the domain interface in the stability, folding and function of CLIC1 - Stoychev, Stoyan Hristov (My University, 2008)
Chloride intracellular channel protein 1 (CLIC1) is a dual-state protein existing in both soluble monomeric conformation as well as integral-membrane form. The role of the domain interface in the conversion between these species was investigated. Bioinformatics-based analysis was undertaken to compare and contrast the domain interfaces of dimeric GSTs with their monomeric homologues CLIC1 and CLIC4. The mutants CLIC1-M32A and CLIC1-E81M were used as experimental case studies on the role of domain-domain interactions in the stability and folding of CLIC family proteins. A consensus interface was revealed with the prominent interaction being a conserved inter-domain lock-and-key type motif previously studied in class Alpha GSTs (Wallace et al., 2000). A number of domain-interface interactions were found to be unique to the CLIC family and as such thought to play a role in the conversion of these proteins from their soluble form to an integral membrane form. Overall the domain interfaces of monomeric CLIC1 and CLIC4 did not differ significantly from the domain interfaces of dimeric GSTs. The removal of the unique CLIC family salt-bridges between Arg29 and Glu81 and the cavity forming domain interface mutation Met32Ala did not induce significant changes in the conformational flexibility of the native state. The true role of the Arg29-Glu81 salt-bridges was masked by the introduction of stabilizing hydrophobic contacts. Removal of the inter-domain lock-and-key interaction destabilized CLIC1 significantly with concomitant loss in cooperative folding that resulted in the stabilization of a molten globule-like species. This intermediate state was less stable and less structured than the equilibrium intermediate of wtCLIC1 at pH 5.5. However the bulk of the structures found to unfold during intermediate-species formation was the same in mutant and wild-type proteins. It was concluded that formation of the membrane-competent form of CLIC1 involves re-structuring of the N-terminal thioredoxin domain that takes place after destabilization of the salt bridges connecting h1 and h3 and uncoupling of the inter-domain lock-and-key motif.
Keywords: Proteins; Membrane proteins; Biochemistry